The problem of meaning in the interpretation of the message ABSTRACT - Osorio Anchiraico, Trixia (2023)
People communicate through signs, verbal or non-verbal; to carry out this end, the speaker createsthe signs and organizes them through language. This process is dominated by the speakers who knowvery well the grammatical rules of their language. On the other hand, the dynamics of communication isthe responsibility of the speaker and the listener and both have an implicit commitment to the encodingand decoding of the message; the first, must build a simple message using the signs; the second,must decipher or interpret this message created by the speaker. This process seems to be simple,however, many times there are difficulties at the time of interpretation by the listener: what does thespeaker mean? In what sense is he saying it? The objective of this article is to analyze and explain theproblem that can arise in the interpretation of the message when there are severalmeanings in the words.